Characterization of Composite RFID Antennas Based on Thermal Properties: A Survey - Chitra Varadhan; Fekadu Ashine Chamatu; S. Arulselvi (Advances in Materials Science and Engineering)
In this paper, a comprehensive survey on thermal and geometric design parameters of composite materials utilized in the fabrication of modern RFID systems has been discussed mainly due to its advantages such as lightweight and high strength. Designing of RF antenna setup requires careful consideration of material, geometric and fabrication parameters. Polymer materials were chosen as the substrate and subjected to extensive studies to determine and predict the capability of the miniaturized RFID antenna. The effect of the polymer matrix composite (PMC) material on the antenna parameters such as gain, bandwidth, and return loss is analyzed and realized that improvement in bandwidth and perfection in impedance matching can be further accomplished by employing fractal structure. It is also discovered that the thermal properties affect the impedance and operating frequencies, thus enabling multilayer PMC deploying fractal structured RFID antennas to be used for many applications such as logistics, aerospace, biomedical, and mining.